2021
DOI: 10.3390/ijerph18168307
|View full text |Cite
|
Sign up to set email alerts
|

Case Fatality as an Indicator for the Human Toxicity of Pesticides—A Systematic Scoping Review on the Availability and Variability of Severity Indicators of Pesticide Poisoning

Abstract: Objective: To investigate if case fatality and other indicators of the severity of human pesticide poisonings can be used to prioritize pesticides of public health concern. To study the heterogeneity of data across countries, cause of poisonings, and treatment facilities. Methods: We searched literature databases as well as the internet for studies on case-fatality and severity scores of pesticide poisoning. Studies published between 1990 and 2014 providing information on active ingredients in pesticides or ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
(45 reference statements)
0
2
0
1
Order By: Relevance
“…In addition, previous studies found that pesticide residues in agricultural products can be transferred to humans through food consumption and contribute to adverse health, including cancer, neurodevelopmental disorders, birth defects, endocrine disruptions, etc. [18][19][20]. Meanwhile, the European Food Safety Authority identified pymetrozine as a possible human carcinogen in 2017 [20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies found that pesticide residues in agricultural products can be transferred to humans through food consumption and contribute to adverse health, including cancer, neurodevelopmental disorders, birth defects, endocrine disruptions, etc. [18][19][20]. Meanwhile, the European Food Safety Authority identified pymetrozine as a possible human carcinogen in 2017 [20].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the runoff into the waterways ensures a high presence and accumulation of both pesticides and herbicides in fish [ 92 ]. Pesticides are highly toxic and, in sufficient concentrations, fatal for humans [ 93 ], while in lower concentrations, they disrupt microbiota and cause serious health problems [ 94 , 95 ].…”
Section: Chemical Contaminants In Feedmentioning
confidence: 99%
“…Sin embargo, el resultado de su aplicación desmedida son los problemas conocidos de resistencia y con el incremento de su empleo se origina un impacto negativo en lo económico, ambiental y social a través del daño a la salud (Maggi, Tang, Black, Marks & McBratney, 2021;Osaili et al, 2022). Está bien documentado y debatido el uso de los agroquímicos como causantes de los efectos teratogénicos, mutagénicos, cancerígenos, hepatotóxicos, neurotóxicos y consecuencias de muerte (Karalexi et al, 2021;Lucero & Muñoz-Quezada, 2021;Matich et al, 2021;Moebus & Boedeker, 2021;Pereira et al, 2021). En los años recientes, el uso de los productos naturales como bioplaguicidas ha resultado ser una herramienta prometedora y rentable, con la capacidad de competir y suplir a los agroquímicos convencionales.…”
unclassified